Cross‐cultural validation of the patient‐practitioner orientation scale among primary care professionals in Spain. (30th October 2020) - Perestelo‐Pérez, Lilisbeth; Rivero‐Santana, Amado; González‐González, Ana Isabel; Bermejo‐Caja, Carlos Jesús; Ramos‐García, Vanesa; Koatz, Débora; Torres‐Castaño, Alezandra; Ballester, Marta; Muñoz‐Balsa, Marcos; del Rey‐Granado, Yolanda; Pérez‐Rivas, Francisco Javier; Canellas‐Criado, Yolanda; et al.
Abstract: Background: In recent decades, many self‐report instruments have been developed to assess the extent to which patients want to be informed and involved in decisions about their health as part of the concept of person‐centred care (PCC). The main objective of this research was to translate, adapt and validate the Patient‐Practitioner Orientation Scale (PPOS) using a sample of primary care health‐care professionals in Spain. Methods: Baseline analysis of PPOS scores for 321 primary care professionals (general practitioners and nurses) from 63 centres and 3 Spanish regions participating in a randomized controlled trial. We analysed missing values, distributions and descriptive statistics, item‐to‐scale correlations and internal consistency. Performed were confirmatory factor analysis (CFA) of the 2‐factor model ( sharing and caring dimensions), scale depuration and principal component analysis (PCA). Results: Low inter‐item correlations were observed, and the CFA 2‐factor model only obtained a good fit to the data after excluding 8 items. Internal consistency of the 10‐item PPOS was acceptable (0.77), but low for individual subscales (0.70 and 0.55). PCA results suggest a possible 3‐factor structure. Participants showed a patient‐oriented style (mean = 4.46, SD = 0.73), with higher scores for caring than sharing . Conclusion: Although the 2‐factor model obtained empirical support, measurement indicators of the PPOS ( caring dimension) could be improved. Spanish primary care health‐care professionals overall show a patient‐oriented attitude, although less marked in issues such as patients' need for and management of medical information.